On the Stability of Cubic and Quadratic Mapping in Random Normed Spaces under Arbitrary T-Norms. (30th April 2014) - Vahidi, J.; Lee, S. J.; Fallah, F.; Ahmadi, R.
Abstract : We prove the stability of some functional equations in the random normed spaces under arbitraryt -norms.